Autologous emulsified fat injection for rejuvenation of scars: A prospective observational study - Lekshmi S. Bhooshan; M. Geetha Devi; R. Aniraj; P. Binod; M. Lekshmi (Indian Journal of Plastic Surgery)
Background: The skin rejuvenation potential of the autologous emulsified nanofat was studied by Tonnard et al. in 2013. This property is due to the viable adipose-derived stem cells present in the nanofat; although, there are no viable adipocytes. The aim of this study was to determine the aesthetic outcome of autologous emulsified nanofat injection in scars using a standardised and validated Patient Observer Scar Assessment Scale (POSAS) and photographs. Materials and Methods: A total of 34 patients with scars of varied aetiologies were included in the study as per inclusion criteria. Pre-operative scoring of the scars with the POSAS scale was done, and photographs were taken. Fat aspiration was done from the lower abdominal wall using syringe liposuction under tumescent anaesthesia. The lipoaspirate was mechanically emulsified, filtered and injected intralesionally into the scar using 26G needle and insulin syringe. Post-operative scar reassessment was done at 3 months with the POSAS scale score and photographs. The improvement in scar characteristics and symptoms were tested statistically using a paired t-test. Pre-operative and post-operative photographic comparison was also done. Results: Out of the 34 patients included in the study, male:female ratio was 22:12. Majority (79.4%) had post-traumatic facial scars. On statistical analysis, there was statistically significant improvement in symptoms such as pain (P = 0.001), itching (P = 0.001), stiffness (P = 0.001), thickness (P = 0.001), colour (P = 0.001), irregularity (P = 0.001) and scar characteristics such as vascularity (P = 0.005), relief (P = 0.001), pliability (P = 0.001), thickness (P = 0.001) and pigmentation (P = 0.001) 3 months after injection. The photographic comparison also showed good aesthetic outcome. Conclusion: Autologous emulsified nanofat injection is effective in improving the scar characteristics as well as symptoms and helps in scar rejuvenation.